Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

What value of [tex]\( x \)[/tex] would make [tex]\( \overline{KM} \parallel \overline{JN} \)[/tex]?

Complete the statements to solve for [tex]\( x \)[/tex].

By the converse of the side-splitter theorem, if [tex]\( \frac{JK}{KL} = \square \)[/tex], then [tex]\( \overline{KM} \parallel \overline{JN} \)[/tex].

Substitute the expressions into the proportion:
[tex]\[
\frac{x-5}{x} = \frac{x-3}{x+4}
\][/tex]

Cross-multiply:
[tex]\[
(x-5)(x+4) = x(x-3)
\][/tex]

Distribute:
[tex]\[
x^2 + 4x - 5x - 20 = x^2 - 3x
\][/tex]

Multiply and simplify:
[tex]\[
x^2 - x - 20 = x^2 - 3x
\][/tex]

Solve for [tex]\( x \)[/tex]:
[tex]\[
x = \square
\][/tex]


Sagot :

To find the value of [tex]\(x\)[/tex] that would make [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex], we can use the side-splitter theorem. According to the theorem, if [tex]\(\overline{KM}\)[/tex] is parallel to [tex]\(\overline{JN}\)[/tex], then the ratio [tex]\( \frac{JK}{KL} \)[/tex] must be equal to the ratio [tex]\( \frac{KM}{MN} \)[/tex].

Given the problem:
[tex]\[ \frac{x-5}{x}=\frac{x-3}{x+4} \][/tex]

Follow these steps to solve for [tex]\(x\)[/tex]:

1. Cross-multiply the given proportion:
[tex]\[ (x-5)(x+4) = x(x-3) \][/tex]

2. Distribute the terms:
[tex]\[ x(x) + x(4) - 5(x) - 5(4) = x(x) + x(-3) \][/tex]
[tex]\[ x^2 + 4x - 5x - 20 = x^2 - 3x \][/tex]

3. Simplify the equation:
[tex]\[ x^2 - x - 20 = x^2 - 3x \][/tex]

4. To eliminate [tex]\(x^2\)[/tex] from both sides, subtract [tex]\(x^2\)[/tex] from both sides of the equation:
[tex]\[ -x - 20 = -3x \][/tex]

5. Solve for [tex]\(x\)[/tex]:
[tex]\[ -x - 20 = -3x \][/tex]
[tex]\[ -20 = -3x + x \][/tex]
[tex]\[ -20 = -2x \][/tex]
[tex]\[ x = \frac{20}{2} \][/tex]
[tex]\[ x = 10 \][/tex]

So, the value of [tex]\(x\)[/tex] that makes [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex] is [tex]\(x = 10\)[/tex]:

Summarizing the steps with the final solution:
- By the converse of the side-splitter theorem, if [tex]\( \frac{JK}{KL} = \frac{KM}{MN} \)[/tex]:
[tex]\[ \frac{x-5}{x} = \frac{x-3}{x+4} \][/tex]

- Substitute the expressions into the proportion:
[tex]\[ \frac{x-5}{x} = \frac{x-3}{x+4} \][/tex]

- Cross-multiply:
[tex]\[ (x-5)(x+4) = x(x-3) \][/tex]

- Distribute terms:
[tex]\[ x^2 - x - 20 = x^2 - 3x \][/tex]

- Simplify and solve for [tex]\(x\)[/tex]:
[tex]\[ x = 10 \][/tex]

Therefore, [tex]\( x = 10 \)[/tex] makes [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex].